The Medieval Chronicle 14
1 online resource.
Keywords: Alongside annals, chronicles were the main genre of historical writing in the Middle Ages. Their significance as sources for the study of medieval history and culture is today widely recognised by historians, by students of literature and linguistics, and by art historians. All chronicles raise such questions as by whom, for whom, or for what purpose they were written, how they reconstruct the past, or what kind of literary influences are discernible in them. With illuminated chronicles, the relation between text and image leads to a wholly different set of questions. The series The Medieval Chronicle , published in cooperation with the Medieval Chronicle Society (medievalchronicle.org), provides a representative survey of on-going research in the field of chronicle studies, illustrated by examples from specific chronicles form a wide variety of countries, periods, and cultural backgrounds.